Translational research for climate resilient, higher yielding crops - Reynolds, Matthew P.; Borrell, Andrew; Braun, Hans; Edmeades, Gregory; Flavell, Richard (Hapres, 2019)
Investment in scientific research is generally asymmetrical: it depends on precedents, current trends in science and technology, and economic, political and social agendas. However, asymmetry occasionally leads to bottlenecks that limit delivery of valuable technologies. This review considers the case of translating plant research to crop genetic improvement. Considerable progress has been made in basic plant science in recent decades fueled largely by the revolution in genetics. Meanwhile, human population has continued to grow exponentially, the natural resource base upon which agriculture depends has diminished significantly, and the climate is becoming less conducive to agriculture in general, especially in already food insecure regions. However, although basic research has delivered promising outputs using model crop species, relatively few new ideas have been tested in a mainstream breeding context. Past successful translational research projects—including enhancing the vitamin A content of maize, increasing the ability of rice to tolerate flooding, approaches for improving the yield potential of spring wheat, and traits for increasing the climate resilience of maize and sorghum—required interdisciplinary and often international collaboration to deliver adequate proofs of concept. They were also driven by a visionary approach and the necessary time commitment from the research institutions and funding bodies involved. These attributes are prerequisite for capitalizing on basic plant research and harnessing it to food security.